Geotechnical earthquake engineering : Geotechnique Symposium in Print 2015 - Haigh, Stuart (Thomas Telford, 2016)
The many large earthquakes of the last decade, including the series in Christchurch in 2010-2011 and the Tohoku earthquake in Japan, have focused even greater attention on the cyclic behaviour of soils during these events. Great advances have recently been made in all aspects of soil dynamics, from the prediction of liquefaction based on site investigation to the impact of shaking on geotechnical systems. The Geotechnique Symposium in Print took place at the Institution of Civil Engineers on 15 June 2015 and provided a forum to discuss the latest advances in the area of geotechnical earthquake engineering. These proceedings bring together the international research presented at the symposium and a number of related papers that were published in earlier issues of Geotechnique.